No sólo ruido y furia. Linchamientos, acciones populares frente a la inseguridad y economías morales de las violencias - Moctezuma Mendoza, Vicente (El Colegio de México, 2019)
This article provides a critique of the common representation of lynchings as a spasmodic and mechanical vision of the actions of popular sectors in the face of insecurity. Not only does this representation establish analytical and explanatory limits for understanding, but, in addition, it reproduces colonial representations of popular subjects and is sustained by making invisible alternative forms of popular responses (violent and non-violent). Recent studies in Latin America have criticized and dismantled various elements of this mechanical representation of lynchings, thereby allowing a more complex understanding of. Nevertheless, it is still possible to identify a common weakness in these analyses: the lack of concern for the specificity of different logics of violence grouped under the term lynching. With this in mind, this paper considers the analytical applicability of the concept of the moral economy of violence in exploring problem.